Comprehensive analysis of thermodynamic properties of calcium nitrate. (July 2019) - Sergeev, D.; Reis, B.H.; Ziegner, M.; Roslyakova, I.; to Baben, M.; Hack, K.; Müller, M.
Highlights: Heat capacity of Ca(NO3 )2 was measured by three different DSC devices. Enthalpy of fusion of Ca(NO3 )2 was measured in a closed Pt-crucible. Molar volume at 0 K was obtained. Bulk modulus was calculated. New thermodynamic dataset for solid and liquid Ca(NO3 )2 is derived. Abstract: Thermodynamic properties of calcium nitrate are of interest for development of thermodynamic databases, which can be applicable for thermal energy storage technologies. In the present work thermodynamic properties of Ca(NO3 )2, i.e. heat capacity ( C p ) and enthalpy of fusion, were determined experimentally. The enthalpy of fusion of Ca(NO3 )2 (33.4 ± 1 kJ/mol) was measured in a closed Pt-crucible at the melting temperature 823 K for the first time. The heat capacity of Ca(NO3 )2 was measured in the temperature range from 143 K to 723 K by three different differential scanning calorimeters. High temperature X-ray diffraction was used for determination of the temperature dependence of volume from 298 K to 723 K. Combination of heat capacity and volume allowed us to calculate the molar volume at 0 K and to obtain the thermal expansion. The Grüneisen parameter and bulk modulus were deduced from combination of the available ab initio values of C v and the values of C p as well as the thermal expansion obtained in this work. This methodology allowed us to perform a comprehensive analysis of experimental values and first principal calculations. A complete thermodynamic dataset for solid and liquid Ca(NO3 )2 has been derived.